The visible and near IR photoluminescent response of nc-Si:Er thin films produced by rf sputtering - Cerqueira, M.F. (2004)
In this contribution we present the visible and near IR photoluminescence (PL) analysis of Er doped nanocrystalline silicon thin films produced by the rf magnetron sputtering method. Efficient photoluminescence was observed in these structures in both the visible and 1.54 µm wavelength regions. We show the strong influence of the presence of a nanocrystalline phase in films on their luminescence efficiency at 1.54 µm, which has been studied for a series of specially prepared samples with different crystallinities, i.e. percentages and sizes of Si nanocrystals. The mechanism involved in the visible photoluminescence of a highly crystalline nc-Si:H sample consisting of about 7 nm silicon nanocrystals embedded in an amorphous matrix is discussed.